TSP-1-CD47-integrin α4β1 axis drives T cell infiltration and synovial inflammation in rheumatoid arthritis - Hu, Jialiang; Wang, Xinmin; Ge, Chuang; Qi, Weiyan; Li, Zeqing; Wang, Yaoyao; Lai, Wenting; Ji, Wei; Xu, Hanmei (Frontiers in Immunology, 2025)
BackgroundImmune cell infiltration into joint synovial tissue and promotion of the inflammatory response are important processes in rheumatoid arthritis (RA). This article delves into the crucial role of CD47 in these processes, as well as the mechanisms at both cellular and molecular levels.MethodsCD47, its ligand TSP-1, and related integrins’ expression was analyzed in RA patients’ synovial and blood samples vs. normals using GEO data. Additionally, a collagen-induced arthritis (CIA) model using Cd47 knockout rats was employed to explore the significant role of CD47 in the arthritic process. This was further validated in wild-type rat CIA model using CD47 antibodies and inhibitors targeting key enzymes in the CD47-activated integrin α4β1 signaling pathway. The crucial role of CD47 in the CIA model and its way of function were investigated at the animal whole-body level, through various joint section analyses, and at the cellular and molecular level.ResultsAnalysis of synovial tissue samples (230 cases) and blood samples (1238 cases) from RA patients in the GEO database showed that the CD47, its ligand TSP-1 and related integrins were significantly overexpressed in RA patients. When Cd47 was knocked out in a rat CIA model, the disease severity of arthritis was significantly alleviated, and the T cell infiltration into rat synovial tissue was remarkably reduced, while the number of B cells, macrophages, and neutrophils did not noticeably change. Mechanistic studies indicated that CD47 on T cells interacts with TSP-1 on vascular endothelial cells in arthritic synovium, activating T cell integrin α4β1. The activated α4β1 binds to VCAM-1, promoting T cell infiltration and inflammatory factor secretion, thereby exacerbating synovial inflammation. The present study also showed that inhibiting the activities of key kinases PKA and Src, through which CD47 mediated integrin α4β1 activation, alleviated arthritis syndromes in CIA rats.ConclusionThe three-molecule model of “TSP-1, CD47 and integrin α4β1” confirmed that CD47 plays an important role in the occurrence and progression of collagen-induced arthritis, a typical animal model of rheumatoid arthritis. Blocking the TSP-1-CD47 interaction or inhibiting CD47-activated integrin α4β1 on T cells could be a potential therapeutic strategy for rheumatoid arthritis.